Challenges in the application of biosensor technology in the clinical biochemistry laboratory - Davoudian, Katharina; Nemtsov, Lidia; Thompson, Michael (Frontiers in Sensors, 2025)
A biosensor device involves the transduction of a surface-oriented biochemical interaction into an electrical signal. This structure offers the potential for obtaining highly specific signals for the assay of bioanalytical targets in a rapid and cost-effective manner. These devices drive a rapidly expanding global market with notable contributions to analysis of blood glucose levels and great potential in the field of personalized medicine. However, some reluctance remains in the application of biosensors in clinical biochemistry laboratories. This article explores these challenges in attempts to highlight opportunities for improvement.